The Role of Islamic Entrepreneurship in Bermuamalah - Moh. Junaidi (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2023)
By looking at reality honestly and objectively, people are aware that cultivating an entrepreneurial mentality is an important breakthrough and cannot be delayed any longer. We all have to think to look and go in that direction. In Islam, both in terms of concept and practice, entrepreneurial activity is not a strange thing, in fact this is what the Prophet, his wife, friends, and also the scholars of the country often practiced. Islam does not only talk about entrepreneurship (although in terms of independent work and hard work), but directly puts it into practice in real life. Educational institutions through their practitioners must be more concrete in preparing learning activity programs that can really encourage the growth and development of an entrepreneurial spirit from elementary school to university.